A municipalização da educação básica no Brasil: um estudo sobre o município de Xaxim (SC) - Silva, Paulo Roberto da (2019)
This is a research about the policies and dynamics of the municipalization of basic education in the municipality of Xaxim (SC), taking as a temporal cut the last thirty years of cooperative federalism in Brazil (1988-2018). The Federal Constitution (CF) of 1988 redesigned the Brazilian State and elevated the municipalities to the condition of federated and autonomous entities, redefining their competences and attributions. Cooperative federalism set the general guidelines for municipalization and held municipalities accountable for implementing and managing a broad set of public policies, including basic education. The study sought to answer the following questions: (i) what policies (national, state and municipal) drove the processes of municipalization of basic education after the 1988 Constitution ?; (ii) what dynamics are present in the process of municipalization of basic education in Xaxim? (iii) what advances and limits characterize the dynamics of municipalization of basic education in the municipality under study? The research was developed through both quantitative and qualitative methods and techniques. Quantitative data were obtained and systematized from the bases of INEP (School Census, IDEB etc), the State Department of Education of Santa Catarina and the Municipal Department of Education of Xaxim. The qualitative research was developed through an extensive literature review and access and systematization of a broad set of photos and documents (Constitution, Laws, Decrees, Ordinances, Minutes, Public Scriptures, Education Plans etc.). Among the various results, the research showed that, since 1988, the Federal Government and the state of Santa Catarina implemented, progressively, a series of policies for the decentralization of competencies to municipalities, with emphasis on Constitutional Amendment 14 / 1996 (FUNDEF); Law 9,394 / 96 (LDB); Constitutional Amendment 53/2006 (FUNDEB); Constitutional Amendment 59/2009; Law 13.005 / 2014 (PNE 2014-2024); State Decree 276/1991; State Decree 2,344 / 1997; Complementary State Law 487/2010 and State Decrees 502 and 671/2011. Given this set of policies, the municipality of Xaxim has implemented numerous expansion actions of the municipal school system. In 2018 the municipal network accounted for: 77% of the total enrollment of the elementary school, being 94% of the enrollments of the initial years and 55% of the final years. According to the data, the municipal network covers 97% of all early childhood education, with 98% of the attendance in kindergartens and 97% of the preschool, in contrast representing 0% of the high school, making a total of 72% of the total attendance of the education. basic. It should be noted that the private network accounts for only 3% of the total attendance of basic education and the state network for 25%.